RESISTANCE TO AMOXICILLIN, CLARITHROMYCIN AND CIPROFLOXACIN OF Helicobacter pylori ISOLATED FROM SOUTHERN BRAZIL PATIENTS - Picoli, Simone Ulrich; Mazzoleni, Luiz Edmundo; Fernández, Heriberto; De Bona, Laura Renata; Neuhauss, Erli; Longo, Larisse; Prolla, João Carlos (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Introduction: Helicobacter pylori is a bacteria which infects half the world population and is an important cause of gastric cancer. The eradication therapy is not always effective because resistance to antimicrobials may occur. The aim of this study was to determine the susceptibility profile of H. pylori to amoxicillin, clarithromycin and ciprofloxacin in the population of Southern Brazil. Material and methods: Fifty four samples of H. pylori were evaluated. The antibiotics susceptibility was determined according to the guidelines of the British Society for Antimicrobial Chemotherapy and the Comité de l'Antibiogramme de la Société Française de Microbiologie. Results: Six (11.1%) H. pylori isolates were resistant to clarithromycin, one (1.9%) to amoxicillin and three (5.5%) to ciprofloxacin. These indices of resistance are considered satisfactory and show that all of these antibiotics can be used in the empirical therapy. Conclusion: The antibiotics amoxicillin and clarithromycin are still a good option for first line anti-H. pylori treatment in the population of Southern Brazil.